Maintenance of good glycaemic control is challenging – A cohort study of type 2 diabetes patient in North Karelia, Finland. Issue 4 (8th February 2019) - Nazu, Nazma Akter; Lindström, Jaana; Rautiainen, Päivi; Tirkkonen, Hilkka; Wikström, Katja; Repo, Teppo; Laatikainen, Tiina
Summary: Aims: This study assessed type 2 diabetes treatment outcomes and process indicators using a comprehensive type 2 diabetes patient cohort in North Karelia, Finland, from 2011 to 2016. Methods: Data from all diagnosed type 2 diabetes patients (n = 8429) living in North Karelia were collated retrospectively from regional electronic patient records. We assessed whether HbA1c and low‐density lipoprotein (LDL) were measured and managed as recommended. Results: The HbA1c measurement rate improved (78% vs 89%) during 2011‐2012 and 2015‐2016, but a gradual deterioration in glycaemic control (HbA1c < 7.0% or 53 mmol/mol) was observed among both females (75% vs 67%) and males (72% vs 64%). The LDL measurement rate initially improved from the baseline. LDL control (<2.5 mmol/L) improved among both females (52% vs 59%) and males (58% vs 66%). A gender difference was observed in the achievement of the treatment target for LDL, with females showing worse control. Conclusions: Low‐density lipoprotein (LDL) control in type 2 diabetes patients has improved, but the existence of gender disparities needs further attention. Maintaining appropriate HbA1c control among type 2 diabetes patients over time appears to be difficult. Active follow‐up and tailored treatment have the potential to improve the quality of care. Electronic patient records could be more efficiently used to improve the quality of care and to support decision‐making.